(untitled) (Research Nepal Journal of Development Studies, 2023)
The study aimed to analyze causes and consequences of social shocks of Khatwe (Marginalized Dalit Community of Dhanusha District) women in Nepal. The quantitative approach and case study research design through household survey techniques were applied. The self-administered questionnaires were filled up by 100 respondents in between January 15 to February 25, 2022. It is an applied descriptive statistical (frequency and Likert scale tabulation) method of data analysis. The study found that Khatwe women are suffering from multiple educational shocks such as Cultural, learning, occupational, and status conscious shocks. Due to the shocks, quality parenting role is not effective that can be noticed in school dropout rate of children and their involvement in household chores. Due to the occupational and status conscious shocks, Khatwe women are encouraging children for joining foreign employment to improve family life and livelihood. However, from learning and cultural shocks, Khatwe children are not getting motivational environment from parents or teachers and compelled to dropouts from higher/educational voyage. The empirical findings are well supported by Marxian perspective on education as well as goral oriented and social capital theories and empirical evidences. Therefore, the study can be a reference for making evidence based policy to the local government for addressing the educational shocks of Khatwe women.